Ports and the environment maritime policy and management - Luo, Meifeng; Yip, Tsz-leung (Routledge, Taylor & Francis Group, 2016)
Ports and the Environment assembles research focusing on the management of ports, and the environmental issues associated with both the shipping trade and the ports themselves. By examining contemporary concerns from the perspectives of maritime policy, port management, and industrial efficiency, this book will be provide important reference for future research and policy-making in this area. This book was originally published as a special issue of Maritime Policy & Management.